Greenfield tunnelling in sands: the effects of soil density and relative depth - Franza, A.; Marshall, Alec M.; Zhou, B. (Thomas Telford ICE Publishing, 2018)
Tunnel construction is vital for the development of urban infrastructure systems throughout the world. An understanding of tunnelling-induced displacements is needed to evaluate the impact of tunnel construction on existing structures. Recent research has provided insight into the complex mechanisms that control tunnelling-induced ground movements in sands; however, the combined influence of relative tunnel depth and soil density has not been described. This paper presents data from a series of 15 plane-strain centrifuge tests in dry sand. The cover-to-diameter ratio, C/D, of the tunnels ranges between 1·3 and 6·3, thereby including relatively shallow and deep tunnels. The sand relative density varies between 30 and 90%, corresponding to loose and dense soils. The effects of C/D, soil density and volume loss on vertical and horizontal soil movements, shear strains and ground reaction curves are discussed. Analysis of surface and subsurface settlement trough characteristics shows that the mechanisms are non-linear and the effects of soil relative density and volume loss on deformation patterns are highly dependent on C/D. The role of soil arching in the definition of the displacement mechanisms and a discussion of the implications of the results to the assessment of damage to existing structures are also provided.